2009
DOI: 10.1097/nen.0b013e3181b66f1b
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration in Different Parkinsonian Syndromes Relates to Astrocyte Type and Astrocyte Protein Expression

Abstract: The reactive changes in different types of astrocytes were analyzed in parkinsonian syndromes in order to identify common reactions and their relationship to disease severity. Immunohistochemistry was used on formalin-fixed, paraffin-embedded sections from the putamen, pons, and substantia nigra from 13 Parkinson disease (PD), 29 multiple-system atrophy (MSA), 34 progressive supranuclear palsy (PSP), 10 corticobasal degeneration(CBD), and 13 control cases. Classic reactive astrocytes were observed in MSA, PSP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 60 publications
17
156
0
2
Order By: Relevance
“…Glial fibrillary acidic protein has been reported to be absent in tufted astrocytes in PSP [58,111]. However, small amounts of GFAP are commonly redistributed around the nucleus in tufted astrocytes in PSP and FTLD-tau.…”
Section: Cytoarchitectonic Changes Linked To Tau Deposits In Astrocytesmentioning
confidence: 99%
“…Glial fibrillary acidic protein has been reported to be absent in tufted astrocytes in PSP [58,111]. However, small amounts of GFAP are commonly redistributed around the nucleus in tufted astrocytes in PSP and FTLD-tau.…”
Section: Cytoarchitectonic Changes Linked To Tau Deposits In Astrocytesmentioning
confidence: 99%
“…Astrocytes are therefore clear candidates to play an important role not only in the maintenance of dopaminergic systems in the healthy brain, but also in the brain affected by Parkinson's disease (PD), a progressive degenerative disorder primarily characterized by the selective loss of dopaminergic neurons in the substantia nigra (SN). The astroglial response is being studied deeply in PD patients and animal models of PD (Morale et al, 2006;Song et al, 2009), but we are still far from understanding it.…”
Section: Introductionmentioning
confidence: 99%
“…The homologues of ApoD in Drosophila, GLaz and NLaz, protect against oxidative damage and contribute significantly to the regulation of longevity (HullThompson et al, 2009;Ruiz et al, 2011;Sanchez et al, 2006;Walker et al, 2006). ApoD is in fact the most robust age dependent up-regulated gene in the brain, conserved across species (de Magalhaes et al, 2009;Loerch et al, 2008), and its expression is boosted by a collection of traumatic, pathological and degenerative nervous system conditions in humans (reviewed by Van Dijk et al, 2006), including Parkinson's disease (Ordonez et al, 2006;Song et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These types of astrocytes are not present in rodents and their metabolic characteristics and functional role remain unknown (Oberheim et al, 2009 The pathological implications of protoplasmic and fibrous astrocytes are poorly understood. Differential sensitivity between protoplasmic and fibrous astrocytes has been described in Parkinson's disease (Song et al, 2009) and cerebral ischemia (Lukaszevicz et al, 2002). A study performed on brain tissue from patients who died with Wilson's disease demonstrated that Alzheimer type II astrocytes originate from the fibrous type of astroglia (Bertrand et al, 2001).…”
Section: White and Gray Matter: Residence To Different Types Of Astromentioning
confidence: 99%